Semantic Knowledge Influences Prewired Hedonic Responses to Odors - Poncelet, Johan (Public Library of Science, 2010)
BACKGROUND: Odor hedonic perception relies on decoding the physicochemical properties of odorant molecules and can be influenced in humans by semantic knowledge. The effect of semantic knowledge on such prewired hedonic processing over the life span has remained unclear. METHODOLOGY/PRINCIPAL FINDINGS: The present study measured hedonic response to odors in different age groups (children, teenagers, young adults, and seniors) and found that children and seniors, two age groups characterized by either low level of (children) or weak access to (seniors) odor semantic knowledge, processed odor hedonics more on the basis of their physicochemical properties. In contrast, in teenagers and young adults, who show better levels of semantic odor representation, the role of physicochemical properties was less marked. CONCLUSIONS/SIGNIFICANCE: These findings demonstrate for the first time that the biological determinants that make an odor pleasant or unpleasant are more powerful at either end of the life span.